EVALUATION OF BRINE SHRIMP CYTOTOXICITY OF 50percent AQUEOUS ETHANOLIC LEAF EXTRACT OF CLITORIA TERNATEA L - Das, Neela; Chatterjee, Padma (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives: To study the anticancerous property of leaves of Clitoria ternatea L. Methods: The leaves were soaked in 50percent aqueous ethanol, extract was filtered and concentrated. Cytotoxicity of the extract was tested by brine shrimp lethality assay. Result: The experimental results revealed that 0.28-0.38percent concentration of 50 percent aqueous ethanolic leaf extract possessed cytotoxic potentiality against brine shrimp. Conclusion: Hence the plant may be identified as a source of bioactive principle having Â antitumour activity. Key words: cytotoxicity, lethal conc., mortality, LC50, brine shrimp, phytochemical products.